2015
DOI: 10.1107/s2052520614026389
|View full text |Cite
|
Sign up to set email alerts
|

The ecstasy and the agony; compression studies of 3,4-methylenedioxymethamphetamine (MDMA)

Abstract: MDMA (3,4-methylenedioxymethamphetamine) is a Class A substance that is usually found in a tableted form. It is only observed in one orthorhombic polymorph under ambient conditions. It shows slight positional disorder around the methlyenedioxy ring which persists during compression up to 6.66 GPa. The crystal quality deteriorates above 6.66 GPa where the hydrostatic limit of the pressure-transmitting medium is exceeded. The structure undergoes anisotropic compression with the a-axis compressing the greatest (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The lack of intercalation and geometry of the hydrogen bonding (sinusoidal pattern rather than a straight chain) permit the hydrogen-bonded chain to act as a spring, something that has been noted in other studies. 46 , 56 The remaining void volumes in both systems, highlighted previously, are the remnants of the void between translated molecules in the hydrogen-bonded chain and hence indicate the lack of intercalation. In Lev, the oxygen of the oxopyrrolidine group is the only part that is in the same plane as the neighboring chain and hence has little effect on the compression along the bond.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The lack of intercalation and geometry of the hydrogen bonding (sinusoidal pattern rather than a straight chain) permit the hydrogen-bonded chain to act as a spring, something that has been noted in other studies. 46 , 56 The remaining void volumes in both systems, highlighted previously, are the remnants of the void between translated molecules in the hydrogen-bonded chain and hence indicate the lack of intercalation. In Lev, the oxygen of the oxopyrrolidine group is the only part that is in the same plane as the neighboring chain and hence has little effect on the compression along the bond.…”
Section: Resultsmentioning
confidence: 71%
“…Both Lev and Eti form layered structures Figure b,d) where strongly hydrogen-bonded layers are stacked through weaker van der Waals interactions. This type of structural feature is important, as previous high-pressure studies have shown that compression is generally observed in the direction perpendicular to the layers due to the lack of strong interactions. , In Lev, the three-dimensional crystal structure is built through translation of the hydrogen-bonded layer along the a direction. The layers have a sawtooth profile when they are viewed along the b direction and interact through weaker van der Waals interactions (−11.6 to −17.1 kJ mol –1 ), where the energy is largely made of a dispersion component (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The structure was solved by direct methods and refined by full-matrix least-squares using the SHELXT program package. 33…”
Section: Single-crystal X-ray Diffractometrymentioning
confidence: 99%
“…While these ultimately lead to degradation of the crystal (e.g. Connor et al, 2015), data collected under non-hydrostatic conditions can be subject to an axial bias in pressure that serves to convolute trends and can promote or supress phenomena such as phase transitions (Ballaran et al, 2013, and references 32À40 therein). Even under hydrostatic conditions, for the majority of high-pressure crystallographic studies of coordination complexes the pressure limit appears to be dictated by the resilience of the sample, with crystals failing to diffract well long before the hydrostatic limit of the PTM is reached (Tidey et al, 2014, and references therein).…”
Section: Pressure Limits Of Studiesmentioning
confidence: 99%